The use of microsatellite markers for parentage analysis in the Pacific cupped oyster, Crassostrea gigas (Thunberg) - Boudry, Pierre; Collet, Bertrand; Kotoulas, Georgios; Magoulas, Antonio; Hervouet, Veronique; Bonhomme, Francois; Gerard, Andre (Actes du colloque, Cascais, Portugal, 16-19 septembre 1998, K: 7, 1998)
Highly polymorphic genetic markers can be useful tools for the analysis of parental contributions. The present paper reports 3 experiments using microsatellite markers to analyse parental contributions in controlled in vitro factorial crosses of the cupped oyster Crassostrea gigas. Parentage analysis was eased by the large polymorphism observed at the 3 loci studied. In a cross between 20 males and 20 females, a quarter of the progeny could be assigned to a given parent using a single microsatellite locus showing 28 alleles. In 3 crosses between 5 males and females, all the progeny could be assigned to a family by using 3 loci. In all cases, the combined genotyping at 2 loci allowed parentage to be detennined unambiguously. Despite the balanced gametic contribution of each parent before fertilisation, unbalanced parental contributions are observed in the progeny, both at larval and juvenile stages. Evidence of gametic and zygotic competition is given to explain the observed unbalanced parental contributions. Les marqueurs génétiques très polymorphes sont des outils très utiles pour l'analyse des contributions parentales. Notre étude présente 3 expériences utilisant les marqueurs microsatellites pour l'analyse des contribution parentales dans des croisement contrôlés in vitro chez l'huître creuse Crassostrea gigas. L'analyse de parenté a été facilitée par le grand polymorphisme observé aux 4 locus étudiés. Dans un croisement entre 20 mâles et 20 femelles, le père ou la mère d'un quart des descendants ont pu être déterminés en utilisant un seul locus microsatellite présentant 28 allèles. Dans 3 croisements entre 5 mâles et 5 femelles, tous les descendants ont pu être assignés à une famille en utilisant 3 locus. Dans tous les cas, la combinaison des génotypes à 2 locus a permis l'identification des parents. Malgré des contributions gamétiques équilibrées entre parents avant la fécondation, des contributions parentales déséquilibrées sont observées dans les descendants, aux stades larvaires et juvéniles. Nous ...